Improvement of high-range-resolution imaging by considering change in ultrasonic waveform during propagation. (25th June 2018) - Mozumi, Michiya; Nagaoka, Ryo; Hasegawa, Hideyuki
Abstract: The range spatial resolution is an important factor determining the quality of the ultrasound B-mode image. In this study, the transmit–receive response of a medical ultrasound system was estimated using ultrasound echoes from an imaging target and used instead of that estimated from an ultrasound echo from a fine wire in water as was done in our previous study. In addition, an estimation procedure of the transmit–receive response was performed region by region to consider the ultrasound attenuation during propagation. From the results using a wire phantom, the range full widths at half maximum (FWHMs) were 0.444 mm (conventional method) and 0.167 mm (our previous method), but it was further improved to 0.150 mm by the proposed method.